Pengaruh ROA, CR, dan DER terhadap PBV Pada Sektor Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020 - Pramana Putra; Eka Purnama Sari (Manajemen Kreatif Jurnal, 2023)
Firm value is the level of success of managers in managing company resources entrusted to them which is often associated with stock prices. This study aims to examine and analyze the effect of ROA, CR, and DER on PBV in food and beverage companies listed on the Indonesia Stock Exchange. The type of research used in this research is quantitative research with a descriptive approach. The samples used in this study amounted to 20 which were taken using purposive sampling method. ROA has no effect on PBV for food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2020 period, CR has no effect on PBV for food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2020 period. DER has no effect on the PBV of food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2020 period. ROA, CR AND DER have no effect on the PBV of food and beverage companies listed on the Indonesia Stock Exchange for the period 2018-2020